2017
DOI: 10.1108/aaaj-02-2015-1965
|View full text |Cite
|
Sign up to set email alerts
|

Corporate anti-corruption disclosure

Abstract: Purpose The purpose of this paper is to investigate whether differences in media exposure regarding corporate corruption appear to influence companies’ anti-corruption disclosures. The authors also examine whether the level of press freedom in firms’ home countries affects disclosure and the impact of media exposure in different ways. Design/methodology/approach The authors use Transparency International’s 2012 ratings of anti-corruption disclosure by the 105 largest multinational firms in the world, press f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 70 publications
4
42
1
Order By: Relevance
“…As a social watchdog, higher media visibility demonstrates corporation concerns over reputation and social legitimacy, which ultimately shows a firm's commitment to fighting corruption. Our finding supports H5 and is consistent with the prior studies of Islam et al [17], Blanc et al [18] and Islam et al [19]. Islam et al [17], who have also investigated the relationship between bribery disclosure and the media visibility of two European mobile corporations, finding a positive and significant association.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As a social watchdog, higher media visibility demonstrates corporation concerns over reputation and social legitimacy, which ultimately shows a firm's commitment to fighting corruption. Our finding supports H5 and is consistent with the prior studies of Islam et al [17], Blanc et al [18] and Islam et al [19]. Islam et al [17], who have also investigated the relationship between bribery disclosure and the media visibility of two European mobile corporations, finding a positive and significant association.…”
Section: Resultssupporting
confidence: 92%
“…As an important stakeholder, corporations seek to maintain a positive relationship with the media by providing different sets of information regarding anti-corruption, anti-bribery, financial integrity and diverse CSR initiatives in order to improve the transparency and accountability of their businesses, as well as to provide sustainable corporate governance practices. Blanc et al [18] have found that media exposure has a positive effect on the anti-corruption disclosure of leading global firms, while the power of media exposure is relatively high in places where there are greater levels of press freedom. Islam et al [19] have shown that two Chinese mobile companies produced more anti-bribe disclosures following international concern, which led to global stakeholder pressure to restore their reputations.…”
Section: Corporate Media Visibility and Ccdmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be argued that because of their geographical extension, international companies are more likely to face greater social pressures. Blanc et al (2017) state that the higher levels of social and political pressure lead companies to use CSRR as a means of reducing their exposures. Some types of social pressures that international companies face include but are not limited to: peaceful and/or violent protests; criticisms and exposure by media; pressure from non-governmental organisations (NGOs); employee strikes; community demonstrations; and boycott of products (Islam, 2015).…”
Section: Introductionmentioning
confidence: 99%